Analisis Perlindungan Konsumen Terhadap Pelanggaran Hak Informasi Pribadi Pada Pinjaman Berbasis Online - Rosedila, Shafa (Proceedings Series on Social Sciences & Humanities, 2024)
Many users of online loan services have complained about the problem of distributing personal data by online loan providers without the applicant's notification or permission. This research aims to analyze how consumer protection in illegal online loan services can misuse borrowers' personal data, because it is important to conduct this research. Even though rules have been made to safeguard personal data, loan service creditors still misuse and disseminate borrowers' personal information, which has an impact negative towards debtors. This research uses normative juridical research with literature. This study is based on applicable laws, previous studies, and legal materials. OJK, ITE, Human Rights, Civil Code and Consumer Protection regulations are some of the laws used.